Recycling of waste Nd-Fe-B sintered magnets by doping with dysprosium hydride nanoparticles - 刘卫强 李超 ZAKOTNIK Miha 岳明 张东涛 黄秀莲 (Journal of rare earths, 2015)
Recycling of waste sintered Nd-Fe-B permanent magnets by doping DyH3 nanoparticles was investigated. The effect of the DyH3 nanoparticles on the microstructure and magnetic properties of the recycled magnets was studied. As the DyH3 nanoparticles additive increased, the coercivity of recycled magnet increased gradually. The recycled magnets with DyH3 nanoparticle content between 0.0 wt.% and 1.0 wt.% maintained the remanence （Br）, but, with higher additions, the Br began to decrease rapidly. The best recycled magnet produced contained 1.0 wt.% of DyH3 nanoparticles when compared to the properties of the starting waste sintering magnet. The Hcj, Br and （BH）max values of 101.7%, 95.4%, and 88.58%, respectively, were recovered.